Prechoroidal Cleft in Type 3 Neovascularization: Incidence, Timing, and Its Association with Visual Outcome - Kim, Jae Hui (J Ophthalmol, 2018)
PURPOSE: To investigate the incidence and timing of prechoroidal cleft development and its association with visual prognosis in type 3 neovascularization. METHODS: This retrospective study included 166 eyes that were diagnosed with type 3 neovascularization. All eyes were treated with antivascular endothelial growth factor therapy. The incidence and timing of prechoroidal cleft development were evaluated. Best-corrected visual acuity (BCVA) at diagnosis and at final follow-up was compared between eyes with (cleft group) and without (no-cleft group) prechoroidal cleft. The incidence of retinal pigment epithelium (RPE) tear and subretinal hemorrhage was also compared between the two groups. RESULTS: During the mean 39.7 ± 18.5 months of follow-up, prechoroidal cleft developed in 37 eyes (22.3%) at an average of 14.6 ± 10.4 months. The BCVA at final follow-up was significantly worse in the cleft group than in the no-cleft group (P=0.024), whereas the difference was not significant at diagnosis (P=0.969). The incidence of RPE tear (P=0.002) and subretinal hemorrhage (P < 0.001) was significantly higher in the cleft group. CONCLUSIONS: Prechoroidal cleft is a frequently observed finding during the treatment course of type 3 neovascularization. Eyes with prechoroidal cleft are at high risk of RPE tear or subretinal hemorrhage and subsequently associated with poor prognosis.